Starring Sally J. Freedman as herself - Blume, Judy (New York : Dell, 1978)
While spending the winter of 1947-48 in Miami Beach with her family, ten-year-old Sally makes up stories, casts herself in starring roles in movies, and encounters a sinister stranger
"Reprinted by arrangement with The Bradbury Press."
Keywords: Family -- Fiction; Jews -- United States -- Fiction; Family life -- Fiction; Jews -- United States -- Fiction